(untitled) (Salud, Arte y Cuidado, 2024)
In the patient, hemodialysis therapy causes changes attributable to the condition of multifactorial etiology, in the case of the skin, it shows variations in skin color, pruritus, xerosis, hair, nails and various dermatoses. The objective of this research was to analyze the skin manifestations in adult patients on chronic hemodialysis, at the Lara II Dialysis Unit. The study is descriptive with a quantitative approach, non-experimental design and cross-sectional. The Population was made up of 38 adult patients with a diagnosis of chronic kidney disease who are included in the hemodialysis program, and come three times a week. Inclusion criteria: patients with more than three months in the hemodialysis program, approve voluntary participation in the study. The technique was the survey and the instrument was a questionnaire designed by the researchers. Results: The average age was 55.8 years; mostly male. Underlying pathology: 91% hypertensive and 80% diabetic. As a personal dermatological history, 43% had seborrheic dermatitis, 51% acne, 3% reported psoriasis and 29% melasma, 97% did not consume NSAIDs or steroids, 11% consumed anti-allergy medications. Regarding allergies to medications: iodine 6%, analgesics 3% and 14% to others, skin biotype 94% dry and 6% normal, skin phototype according to the Fitz-Patrick classification 31% III, 57 IV and 11% V, 94% with an average of 257.43 calcium and 8.79 and 4.62 phosphorus respectively and average hemoglobin of 9.89 g/dL. 51% of patients present pruritus. It is concluded that, with the advent of increasingly effective renal replacement therapies, the frequency of skin disorders in patients with CKD is maintained.